Investigation of the phreatic aquifer development at the Pinios Delta basin (Thessaly), through a combination of geophysical and hydrogeological data - Alexopoulos, J.D.; Matiatos, I.; Dilalos, S.; Vassilakis E.; Panagopoulos, Α.; Ghionis, G.; Poulos, S. (10th Congress of the Hellenic Geographical Society, 2014)
The present study aims to clarify the hydrogeological regime of the phreatic aquifer, primarily its spatial distribution, through a combined interpretation of the preliminary results of an extensive geophysical research conducted in the area and of the hydrogeological data collected in parallel scientific actions by previous researchers. In the context of the geophysical research that was carried out in the region, 37 Vertical Electrical Soundings, investigating the resistivity distribution (Schlumberger array), were performed during May and October 2013. Moreover, previous periodic measurements of the groundwater level of the phreatic aquifer and hydrochemical analysis were taken into consideration. The preliminary results of the geophysical data processing indicate that the phreatic aquifer is not detected throughout the whole deltaic plain but extends mainly in the central and northern parts of the region. Most of the investigated sites showed that the hosting formation’s thickness is limited up to 10 meters, since the underlying geoelectrical formation (20-40 Ohm.m) is believed to be an impermeable formation. The literature-derived hydrogeological data also indicate that the depth of the phreatic aquifer is generally small. In particular, the groundwater monitoring showed that the water table did not exceed 4m in depth. Moreover, the hydrochemical data indicated a limited seawater intrusion, which seems to be controlled by the hydraulic head of the groundwater and the sedimentological composition of the dune system covering the coastal zone, which is also indicated by the geophysical results.